The Role of Civil Servants in Strengthening Religious Moderation for the Sustainability of Islamic Da‘wah in the Modern Era: A Case Study at the Bandung Religious Training Center - Ega Diah Pridayanti; Haidar Ainurrahman; Dadan Suherdiana (JENTRE, 2026)
This study examines the role of the State Civil Apparatus (Aparatur Sipil Negara / ASN) in strengthening religious moderation to support the sustainability of Islamic da’wah in the modern era, with a case study at the Bandung Religious Training Center (Balai Diklat Keagamaan / BDK Bandung). It is motivated by contemporary challenges to Islamic da’wah, including the proliferation of extremist narratives in digital spaces, generational shifts, and the complexities of Indonesia’s pluralistic and multicultural society. Using a qualitative case study approach, data were collected through in-depth interviews with widyaiswara at BDK Bandung, as well as analysis of training practices and the implementation of moderation values by ASN, particularly religious counselors. The findings indicate that ASN plays a strategic dual role as both public service agents and da’wah actors in disseminating key values of religious moderation, namely national commitment, tolerance, non-violence, and respect for local wisdom. Training in religious moderation significantly shapes the mindset, attitudes, and professional practices of ASN, enabling them to deliver Islamic da’wah in a more moderate, adaptive, and context-sensitive manner. This study concludes that strengthening religious moderation through ASN extends beyond policy implementation and constitutes a critical foundation for fostering inclusive, relevant, and sustainable Islamic da’wah in the context of rapid social and technological change.